On the symmetry axiom for values of nonatomic games - Dov Monderer; William H. Ruckle (International Journal of Mathematics and Mathematical Sciences)
In this paper, a weaker version of the Symmetry Axiom on BV, and values on subspaces of BV are discussed. Included are several theorems and examples.